Novel Dual Band Microstrip Circular Patch Antennas Loaded with ENG and MNG Metamaterials - Md. Ababil Hossain; Md. Saimoom Ferdous; Shah Mahmud Hasan Chowdhury; Md. Abdul Matin (International Journal of Antennas and Propagation)
Novel design of a dual band microstrip circular patch antenna loaded with ENG (ε negative) metamaterial has been shown in the first section. Using ENG metamaterial instead of the conventional dielectric, unconventional TMδ10 (1<δ<2) mode was produced to yield a dual band performance. Optimized parameters such as permittivity (ε1) and filling ratio (η) of metamaterials were selected with the aid of a MATLAB based parameter optimization algorithm, developed for all these sort of patch antennas. In the second section, a dual band circular patch antenna loaded with MNG (µ negative) metamaterial has been reported. An unconventional modified TMδ10 (0<δ<1) mode has been produced along with conventional TM110 mode due to using MNG metamaterial. Here also the optimum values of permeability (µ1) and filling ratio (η) for these sorts of patch antennas have been calculated from a MATLAB based parameter optimization algorithm. Both the proposed antennas provide good and resonance and satisfactory radiation performances (directivity, radiation efficiency, and gain) with a dual band performance.